OP64 Do religious practices and beliefs moderate the association between stressful life events and subsequent mental health and wellbeing?. (2nd September 2017) - Kaushal, A; Cadar, D; Stafford, M; Richards, M
Abstract : Background: Religion may provide coping strategies for stressful life events (SLEs). Aspects of religious practices and beliefs, e.g. provision of meaning in life, interpretation of difficult events and supportive social contact can all contribute to successful coping strategies. The aim of this project was to investigate if SLEs are associated with mental health and wellbeing in early old age and if religious practices and beliefs moderate these associations. Methods: Participants were study members from the MRC National Survey of Health and Development (1946 British birth cohort) who participated in data collection at age 68–69 (n=2148). Mental health and wellbeing were measured using the 28-item General Health Questionnaire and the Warwick-Edinburgh Mental Wellbeing Scale. SLEs were measured using a checklist of events on five occasions from age 26 to 60–64. Religious practices and beliefs were ascertained from age 11 to 68–69 and included upbringing, beliefs and attendance. Initial analyses investigated associations between SLEs, and mental health and wellbeing. This was followed by analyses to determine if religious practices and beliefs were more common in people who had good mental health or high wellbeing despite experiencing a high number of SLEs compared to those with fewer SLEs and poor mental health or wellbeing. Analyses were conducted using linear and logistic regression models adjusted for gender and education. Results: Experiencing SLEs was associated with lower wellbeing (β=−0.31, CI=−0.46, –0.16) and worse mental health at age 68–69 (β=0.02, CI=0.02, 0.03). High wellbeing at age 68 despite a substantial number of SLEs was associated with frequent religious attendance (for men only) from age 36 to 60–64 (OR=2.60, CI=1.10, 6.14), religious importance (OR=1.83, CI=1.13, 2.97) and meaning in life provided by religion (OR=2.07, CI=1.31, 3.29). There were no differences in religious practices and beliefs between study members with good mental health and a high number of SLEs compared to those with fewer SLEs and poor mental health. Conclusion: SLEs across the life course were associated with poor mental health and wellbeing in early old age. We also found evidence that religious practices and beliefs moderate the effect of SLEs on wellbeing but not mental health, and in particular that religious attendance is beneficial for men and not women. Future work will investigate if SLEs are associated with changes in religious attendance, mental health and wellbeing, and if this varies by different types of SLEs, e.g. personal and interpersonal, health and work-related events.